Regulatory Policies for Demand-Driven Innovation by Heterogeneous Firms - LIN, Mei (Institutional Knowledge at Singapore Management University, 2010)
We investigate the innovation rate under the impact of business cycles to understand R&D activities and to derive implications for public policies. Combining price competition and endogenous market structure with the framework of dynamic game, we study the Markov perfect equilibrium where heterogeneous firms choose whether to participate in the innovation race and the innovation rate. Based on the analytical results derived from the price competition, we find that increased income per capita tends to improve aggregate innovation, while incumbents reduce their innovation efforts as more entrants enter the innovation race, the competition pressure increases. Income inequality shocks may reduce or have no impact on innovation, depending on equilibrium region. We find subsidies to reduce innovation incentive, and policies such as tax incentives that reduce the variable R&D costs to have consistently positive effects. Our findings on both the income shocks and policies are consistent with the empirical evidences.